Performance and emission of swirl burner with different swirl numbers using palm, coconut and jatropha oil biodesel - Norwazan Abdul Rahim (Tesis, 2017)
The aim of this research is to determine the most suitable percentages of biodiesel fuel blends to be combined with the swirler vane angle in the liquid fuel burner. Therefore, experimental works were conducted in this study by using swirl burner